Determination of the accelerated heavy ions registration threshold in multilayered polymeric films - Vorobyova, I.V.; Zajtsev, B.V.; Kobets, A.P. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
As detectors high-energy ions polymeric films from polyethyleneterephthalate (PETF) were used. Films were irradiated on the Kharkov heavy ions linear accelerator MILAC with the accelerated ions of nitrogen and argon with energy of 1 MeV/u. Multilayered samples consisted of polymeric films of a various thickness contacting with each other (3,6,10 μm) from which various combinations of thickness of contacting films were made. For revealing of tracks after irradiation samples were handled in an alkali solution. Methods of optical microscopy investigated surfaces of films and formation of tracks by the accelerated ions of argon and nitrogen was compared. Researches are carried out and thresholds of registration of the accelerated ions of an argon and nitrogen in multilayered PETF films are spotted depending on energy losses. В качестве детекторов высокоэнергетичных ионов использовались полимерные плёнки из полиэтилентерефталата (ПЭТФ). Пленки облучались на Харьковском линейном ускорителе тяжелых ионов ЛУМЗИ ускоренными ионами азота и аргона с энергией 1 МэВ/нукл. Многослойные образцы состояли из контактирующих друг с другом полимерных пленок различной толщины (3,6,10 мкм) из которых составлялись различные комбинации толщин контактирующих пленок. Для выявления треков после облучения образцы обрабатывались в растворе щелочи. Методами оптической микроскопии исследовались поверхности пленок и проводилось сравнение формирования треков ускоренными ионами аргона и азота. Проведены исследования и, в зависимости от энергетических потерь, определены пороги регистрации ускоренных ионов аргона и азота в многослойных ПЭТФ плёнках. Як детектори високоенергетичних іонів використовувалися полімерні плівки з поліетилентерефталату (ПЕТФ). Плівки опромінювалися на Харківському лінійному прискорювачі важких іонів ЛУМЗІ прискореними іонами азоту і аргону з енергією 1 МеВ/нукл. Багатошарові зразки складалися з контактуючих одна з одною полімерних плівок різної товщини (3,6,10 мкм). Для виявлення треків після опромінення зразки оброблялися в розчині лугу. Методами оптичної мікроскопії досліджувалися поверхні плівок і проводилося порівняння формування треків прискореними іонами аргону та азоту. Проведено дослідження методами оптичної мікроскопії і залежно від енергетичних втрат визначені пороги реєстрації прискорених іонів аргону і азоту в багатошарових ПЕТФ плівках.